How do the effects of local growth on employment rates vary with initial labor market conditions? - Timothy J. Bartik (W.E. Upjohn Institute for Employment Research, 2009)
This paper examines how the effects of increased employment growth on a metropolitan area's employment to population ratio varies with the initial tightness of the metropolitan area's labor market. This examination is relevant to evaluating the benefits of local economic development policies in different metropolitan areas. Much of the benefits of such policies are in higher employment rates. The empirical estimates suggest that the effectiveness of employment growth in increasing the employment to population ratio is lower in metropolitan areas with 'tight' labor markets. In addition, some estimates suggest that growth has the greatest long-run effects on the employment to population ratio in metropolitan areas with some looseness in labor market conditions, compared to metropolitan areas with the most tight or most loose labor market conditions. Growth pays off the most for metropolitan areas that have above-average labor market problems, but not too much above average.
Keywords: R23; J61; 330